The Wandering Jew as Monster: John Blackburn’s Devil Daddy - Lisa Lampert-Weissig (Humanities)
Can we think of the legendary Wandering Jew as a monster? The figure does not easily fit the common definition of a monster and yet, the Wandering Jew is extraordinary. In the medieval and early modern sources of the legend, the Wandering Jew, who once sinned against Christ and is therefore doomed to be an immortal eyewitness to the Passion, serves as a model for the faithful. In his 1796 gothic novel, The Monk, Matthew Lewis creates a new strand of the Wandering Jew tradition, a gothic Wandering Jew, a being transformed from wonder to horror through association with centuries of antisemitic accusations against Jews as agents of conspiracy, ritual murder, nefarious magic, and disease. This essay argues that a variation on the representation of the gothic Wandering Jew, which began with Coleridge’s Rime of the Ancient Mariner, further adapts the legend to make the Wanderer not a sign of redemption, but the monstrous cause of catastrophe not only for himself, but for those he encounters. This article, the first scholarly examination of John Blackburn’s 1972 Wandering Jew novel, Devil Daddy, situates it within the strand of the legend that represents the Wandering Jew as a monstrous source of destruction. Blackburn’s novel, written during a time of global concern over the development of biological weapons of mass destruction, portrays the Wandering Jew’s curse as a source of manmade global environmental catastrophe. In this way, the sin of the monstrous Wandering Jew becomes one not against Christ, but against humankind. Even as Devil Daddy explicitly references the horrors of the Holocaust, this representation of a monstrous Wandering Jew haunts the text, undermining its sympathetic representation of Jewish suffering.